1988
DOI: 10.2118/11740-pa
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interfacial Tension on Gas/Oil Relative Permeability in a Gas-Condensate System

Abstract: To understand better the effect of interfacial tensions (1FT's) on gas/oil relative permeabilities, with particular emphasis on those effective in condensate reservoirs, an experimental procedure was developed and used with the highly volatile methane/propane system. The objective was to measure steady-state relative permeabilities as functions of 1FT. Thus the 1FT was varied from 0.03 to 0.82 dynes/cm [0.03 to 0.82 mN/m], corresponding to pressures near the critical at a constant temperature of 70 D F [21 DC]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(71 citation statements)
references
References 13 publications
2
67
0
Order By: Relevance
“…IFT reduction will alter the relative permeability and influences each phase flow behavior [10][11][12][13][14]. In a numerical study on chemical injection it was observed that the relative permeability curve can be represented by 4 curves that are obtained from measurements and show 2 extreme and 2 transition conditions ( Figure 1) [9].…”
Section: Figurementioning
confidence: 99%
“…IFT reduction will alter the relative permeability and influences each phase flow behavior [10][11][12][13][14]. In a numerical study on chemical injection it was observed that the relative permeability curve can be represented by 4 curves that are obtained from measurements and show 2 extreme and 2 transition conditions ( Figure 1) [9].…”
Section: Figurementioning
confidence: 99%
“…The maximum length for flow, h max , is directly proportional to interfacial tension from Eq. [3]. But the saturation needed to make a cluster of length h max is not linear with h max .…”
Section: Fig 10 Effect Of Coordination Number (Cm)mentioning
confidence: 99%
“…An equation for determination fracture network permeability was developed . Effect of surface tension on gas and condensate relative permeability was investigated (Asar and Handy 1988). A gas condensate reservoir including a mixture of three hydrocarbons with compositional and fully implicit method was modeled (Jones and Raghavan 1988).…”
Section: Introductionmentioning
confidence: 99%